Anorectal Malformations: Histomorphological and Immunohistochemical Evaluation of Neuronal Dysfunction - Yashika Bhatia; Sunita Singh; Kamal Nain Rattan; Padam Parmar; Divya Sahni; Rajeev Sen (EL-Med-Pub, 2017)
Objective: The patients with anorectal malformations (ARM) have been identified with specific and non-specific pathological changes. The present study was conducted with the aim to study histomorphological changes and various immunohistochemical (IHC) markers (calretinin, S-100, CD117) in intestinal wall specimens to assess neuronal dysfunction in ARM patients. Material and methods: Thirty children having ARM were included in our study. In all the cases, a representative biopsy was received. The tissue sections were processed and wax blocks were prepared. Various histopathological changes were examined on routine H&E. Representative sections were further subjected to IHC staining for ganglion cells (calretinin), interstitial cells of Cajal (CD117) and nerve bundles (S-100 protein). Descriptive variables were analyzed to assess neuronal dysfunction in cases of ARM. Chi-square was used to compare the categorical values. P-valueResults: Biopsies were studied for histological changes using H&E stain. The most frequently observed histological finding in mucosa was inflammation and congestion in 87% and 67% of cases respectively. Disrupted muscularis mucosa was observed in 60%, eroded mucosa in 57%, and hemorrhage in 40% of cases. Submucosal inflammation and congestion were most common finding observed in submucosa in 87% and 80% cases respectively. CD117 was used to demonstrate altered density and distribution of interstitial cells of Cajal (ICC) in cases of ARM. Majority of them belong to grade 2+ category (n=17, 57%) followed by grade 1+ (n=8, 17%) for ICC cells. Altered density and distribution of ICC was observed in ARM which was statistically significant (p=0.02). Conclusion: The malformed segments in ARM show various specific and non-specific histomorphological changes. Examination of H&E sections along with IHC stains evaluation can minimize need for repeated biopsies and unnecessary radical treatment. CD117 immunohistochemistry is reliable adjunctive test in evaluation of ICC in motility disorders of bowel. Calretinin is good marker for identification of ganglion cells. In ARM, density and distribution of ICCs is significantly altered which can explain postoperative dysmotility.